Analysis of Mudharabah Financing on the Profitability of Bank Permata Syariah Surabaya - Naini Munawaroh; Anik Siti Istikomah; Sumira Husen; Ilmagita Afrilea; Andi Azhari L. (Majapahit Journal of Islamic Finance and Management, 2022)
This study aims to find out whether mudharabah financing helps in increasing profitability at Bank Permata Syariah Surabaya. The type of research used is qualitative research because this research is mini-research in nature, where researchers have to meet directly with informants and through a literature study method where data sources are taken and collected from books, journals, previous research, or websites which are then read and processed into the material. The study based on results of the study found that mudharabah financing also helped increase the profitability of Bank Permata Syariah Surabaya. There are several factors that influence the decline in mudharabah financing in increasing profitability including decreasing customer interest in mudharabah financing and increasing customers experiencing financing problems.